A comprehensive retrospective study of the seroprevalence of H9N2 avian influenza viruses in occupationally exposed populations in China - Li, Xin (PLoS One, 2017)
The H9N2 avian influenza virus circulates worldwide, predominantly in poultry. Its increasing infectivity and adaptation in poultry and mammals have enhanced the possibility of human infection. However, H9N2 human cases are difficult to detect due to their mild clinical symptoms. Serological study is valuable for risk assessment. A total of 15,700 serum samples were collected from occupationally exposed populations in 22 provinces of China and tested using hemagglutination inhibition (HI) and microneutralization (MN) assays. The sera positive rate of A/Guangzhou/333/99 (G9) was significantly higher than that of A/quail/Hong Kong/G1/97 (G1) (p<0.0001). The seroprevalences of H9N2 were significantly higher in live poultry market workers, large-scale poultry farmers and backyard farmers than in poultry slaughtering factory workers and wild bird habitant workers. The seroprevalences of A/Guangzhou/333/99 (G9) (3.42%) and A/quail/Hong Kong/G1/97 (G1) (1.37%) in Southern China were significantly higher than those in Northern China (p<0.001). The seroprevalence was highest in the elderly, followed by adults and then youths. Our results indicate that subclinical human infection with H9N2 avian influenza virus is widely distributed in China. Longer poultry exposure might contribute to the higher seroprevalence in the elderly group. The higher seroprevalence observed in Southern China than in Northern China might be caused by a higher poultry density.